Evaluation of Merkel cell polyomavirus in non-small cell lung cancer and adjacent normal cells. (July 2017) - Behdarvand, Anahita; Zamani, Mohammad Saber; Sadeghi, Farzin; Yahyapour, Yousef; Vaziri, Farzam; Jamnani, Fatemeh Rahimi; Nowruzi, Bahareh; Fateh, Abolfazl; Siadat, Seyed Davar
Abstract: Several risk factors have been linked to lung cancer (LC). Nevertheless, a viral etiology has been mentioned for a subset of patients developing LC. The aim of this study was to evaluate the effect of Merkel cell polyomavirus (MCPyV) on developing non-small cell lung cancer (NSCLCs). In total, 96 paraffin-embedded NSCLC biopsies and 96 adjacent non-LC normal specimens were analyzed by quantitative real-time polymerase chain reaction (PCR) for the existence of the MCPyV DNA and the expressions of RNA transcripts. Among the 96 enrolled participants, 42 patients were adenocarcinomas (ADs) and 54 patients were squamous cell carcinoma (SCC). Of the 42 ADs, MCPyV DNA was determined in 15 (35.7%) samples and of the 54 SCC, MCPyV DNA was detected in 22 (40.7%) samples. Only one non-cancerous sample in SCC subjects was positive for MCPyV LT -Ag DNA load (0.216 × 10 −3 ). In MCPyV-positive subjects, the median MCPyV copy number was higher in the patients with ADs (0.016 × 10 −3 copies/cell) compared to SCCs (0.005 × 10 −3 copies/cell); but this difference was not statistically significant ( P  = 0.913). In the seven stages of LC, the MCPyV LT -Ag was quantified in stage IV (0.204 × 10 −3 copies/cell) more than in other stages. There was statistically significant difference between stages of cancer and MCPyV LT -Ag DNA load ( P  = 0.002). These results revealed for the first time the presence of MCPyV in a subset of patients with NSCLCs in Iran. Further studies should be carried out to clarify the role of MCPyV in lung carcinogenesis. Highlights: Prevalence of MCPyV infection in lung cancer is moderate. Median MCPyV copy number was higher in the patients with ADs compared to SCCs. MCPyV is associated with stages of lung cancer.